The use of transitology in the field of transitional justice: a critique of the literature on the ’third wave’ of democratisation - Grosescu, Raluca (Historein, 2015)
This article analyses the role and the limits of transitology in framing transitional justice studies after the collapse of dictatorial regimes in Southern Europe, Latin America and Eastern Europe. It examines the evolution of the scholarship with reference to three main topics that have been pioneered by transitologists and developed further by transitional justice scholars, namely: the connections between justice for past abuses and democratisation; the determinants of transitional justice; and the relationship between accountability and the passage of time. The article argues that while transitology has nurtured important research initiatives in the field of transitional justice, its approaches suffer from serious shortcomings. They remained overly prescriptive and short-term in focus, and they often dehistoricised social phenomena. Adopting a teleological perspective on transitions supposedly bound for democracy, they overlooked comparisons and interconnections between transitional justice processes originating in democratic contexts and those arising from dictatorial settings. Moreover, in their attempt to build general typologies and establish causalities between types of dictatorial regimes, exit modes from authoritarianism and justice mechanisms, transitological approaches often failed to explain the peculiarities of national cases, and likewise paid scant attention to international contexts and transnational interactions.